DEVELOPMENT OF HALAL TOURISM AREA ON BANTAYAN BEACH SENEUDON - Ramadhan Razali; Riska Mahqdalena (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2023)
Increasing the halal industry is carried out through various efforts by the government. One sector that has escaped the government's attention is the tourism sector. This study aims to determine the development of halal tourism on Bantayan Beach. Data collection was done by interview technique. The respondents in this study were business owners and local government. The findings from this study are that Bantanyan Seunudon Beach has made efforts to create halal tourism. The illustration and construction can be seen from the provision of sharia-based places, the construction of sharia culture, and sharia facilities.